Role of Virechana Karma in a Case of Vipadika w.s.r to Palmoplantar Psoriasis (AYUSHDHARA, 2025)
Skin diseases of any form bring about huge social stigma along with the pain or trauma caused by the disease itself. This not only affects one’s physical health but also significantly disrupts self-esteem and quality of life. Psoriasis is an auto-immune disorder affecting 2-5% of the total population out of which 3-4% are affected by palmoplantar psoriasis, a variety of the disease where only the palm and sole is affected. In Ayurveda, this variety of psoriasis has been described as Vipadika, often associated with vitiation of Vata and Kapha doshas, leading to dryness, thickening of skin, and painful fissures. In this study, a female patient came to OPD with complaints of dry rashes in hands and foot was examined and after diagnosis was subjected to Virechana showing remarkable results on follow-up after 15 days.